Peningkatkan Kreativitas Dalam Kegiatan Meronce Melalui Media Lingkungan Sekitar Pada Anak Didik Kelompok B Semester Ganjil TK Pertiwi 2 Sumurboto Jepon Kabupaten Blora Tahun Pelajaran 2015/2016 - Sukowati, Sri, Drs. M. Yahya, M.Si (2015)
This study aims to improve the ability of children's creativity through the media meronce surrounding environment. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children Group B TK Pertiwi 2 Sumurboto District of Jepon Blora totaling 20 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about the ability of children's creativity meronce and data on teacher learning through activity. Both of these data were collected through observation. Data were analyzed children's ability meronce creativity with comparative analysis and data on teacher learning through activities surrounding environment is analyzed by interactive analysis. The results of the analysis showed that the average prasiklus meronce child's creative abilities reached 45% means that the ability of children's creativity meronce just beginning to develop. After the first cycle measures the average ability of creativity meronce child reaches 66%, which means that the ability of children's creativity meronce already increased to evolve as expected. After the second cycle measures the average ability children's creativity meronce increased 90% means the ability of developing children's creativity meronce very baik.Kesimpulan of this study is that through the media surrounding environment could improve children's creativity meronce in group B TK Pertiwi 2 Sumurboto District of Jepon Blora.